Unintentional pediatric submersion-injury-related hospitalizations in the United States, 2003. Issue 2 (3rd April 2008) - Cohen, R H; Matter, K C; Sinclair, S A; Smith, G A; Xiang, H
Abstract : The objective of this study was to examine the demographic characteristics and hospital resource utilization of submersion-injury-related hospitalizations among persons ⩽20 years of age in the USA in 2003. All 1475 pediatric submersion-injury-related hospital discharges in the Kids' Inpatient Database were identified by ICD-9-CM diagnosis code or external cause of injury code. These cases represent an estimated 2490 pediatric submersion-injury-related hospitalizations nationwide. Inpatient costs for these estimated hospitalizations were ∼$10 million. The overall pediatric submersion-injury-related rate of hospitalization was 3.0 per 100 000 persons. Children aged 0–4 years had the highest rate of hospitalization (7.7 per 100 000 persons). Children with permanent submersion-injury-related morbidity accounted for 5.8% of hospital admissions and 37.3% of hospital costs in our study, and children with submersion-injury-related in-hospital death accounted for 11.6% of hospital admissions and 20.0% of hospital costs in our study. Prevention of submersion injury using focused, proven strategies deserves increased attention.